Varicella with Delayed Hemiplegia - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1990)
Acute hemiplegia developed seven weeks to four months after varicella infection in four children reported from the Division of Child Neurology, Institute of Neurological Sciences, Tottori University School of Medicine, Yonago, Japan.